Sharing International Commercial Law across National Boundaries, Festschrift for Albert H. Kritzer on the Occasion of his Eightieth Birthday - Pansiri, Melissa Ann (Journal of Law and Commerce, 2009)
The joint collaboration of Camilla B. Andersen and Ulrich G. Schroeter as editors of the festschrift1 to Albert H. Kritzer on his eightieth birthday succeeds in bringing together international commercial law heavyweights and enlightening commentary on the United Nations Convention on Contracts for the International Sale of Goods (CISG). The work pays homage to a preeminent scholar on the CISG whose scholarship has aided in the uniformity of the application and interpretation of the CISG.